Lecturing materials generating tools (LMaGTool): Tools to support notes generating task / Law Yong Sein - Law , Yong Sein (2002)
Education is always a concern of everyone, especially educator like teachers, lecturers and tutors. To ensure their students learn more efficiently, they need a set of good teaching materials. Learning Material Generating Tool (LMaGTool) is a tool that provides various features to help them produce better teaching materials in shorter time. This tool is designed to operate under Microsoft Office applications environment, which is their familiar environment. Teaching programming language is more efficient with materials generated by LMaGTool. Codes can be displayed highlighted, and focused block-by-block, line-byline or word-by-word. A code simulator will help student to understand the code execution more thoroughly. LMaGTool consist of two parts, content editing tools and content displaying tools. By using content editing tools, users can edit learning materials easier and they can include some dynamic contents in these materials. While editing material content getting more efficient, displaying task also been optimized with special designed displaying features to support dynamic contents prepared by the editing tool. This project is proposed to develop using Visual Basic for Applications, a language shipped with Microsoft Office that allows office development. All of the features have been building to deal with Office objects. It is believed that this tool will become an efficient tool to generate learning materials.